2014
DOI: 10.1016/j.ygeno.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability, promoter methylation and protein expression of the DNA mismatch repair genes in epithelial ovarian cancer

Abstract: The role of defective mismatch repair (MMR) system in ovarian carcinoma is not well defined. The purpose of the study was to determine the relationship between microsatellite instability (MSI), promoter methylation and protein expression of MMR genes in epithelial ovarian carcinoma (EOC). MSI and promoter methylation of MLH1, MSH2 and PMS2 genes were studied using PCR methods in the study cohort. A small subset of samples was used to analyze the protein expression by immunohistochemistry (IHC). MSI was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
0
20
0
3
Order By: Relevance
“…The extra band originated from one of two alleles with the characteristic stutter at one or more repeat unit below the main signal and the new allele differed from the assigned ancestral allele by one repeat. Microsatellite instability (MSI) was reported in leukemia [25], gastric [26], ovarian [27], breast [28], and colon cancers [29]. A total of 32 cell lines with MSI were identified with three banding patterns, including 7 liver cancer cell lines, 8 cervical cancer cell lines, 2 ovarian cancer cell lines, 1 leukemia cell line, 3 stomach cancer cell lines, 4 breast cancer cell lines, 1 colon cancer cell line, 2 osteosarcoma cancer cell lines, 1 pancreatic cancer cell line, 1 kidney cell line, 1 lung cancer cell line and 1 lymph cancer cell line.…”
Section: Resultsmentioning
confidence: 99%
“…The extra band originated from one of two alleles with the characteristic stutter at one or more repeat unit below the main signal and the new allele differed from the assigned ancestral allele by one repeat. Microsatellite instability (MSI) was reported in leukemia [25], gastric [26], ovarian [27], breast [28], and colon cancers [29]. A total of 32 cell lines with MSI were identified with three banding patterns, including 7 liver cancer cell lines, 8 cervical cancer cell lines, 2 ovarian cancer cell lines, 1 leukemia cell line, 3 stomach cancer cell lines, 4 breast cancer cell lines, 1 colon cancer cell line, 2 osteosarcoma cancer cell lines, 1 pancreatic cancer cell line, 1 kidney cell line, 1 lung cancer cell line and 1 lymph cancer cell line.…”
Section: Resultsmentioning
confidence: 99%
“…In epithelial ovarian cancer, microsatellite instability (MSI) was observed in 14.9% of cases in a series of 834 samples [ 38 ]. MSI can be due to germline mutation within at least one of four mismatch repair genes ( MLH1 , MSH2 , MSH6 , and PMS2 ), but more likely to hypermethylation of the MLH1 promoter in sporadic cancers, including ovarian cancers, with an occurrence of 37.5% [ 39 ]. With the exception of germ cell tumors, hypermethylation of MLH1 was observed in more than half of our series of ovarian epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether MSI is a reliable proxy for loss of MMR in ovarian cancer. Some studies have identified MSI-H in more than 60% of ovarian epithelial tumors, while MMR protein expression was intact in a subset of these cases [ 30 ], and MSI is also found in more than 50% of normal ovarian tissues [ 30 31 ]. Other studies have found a lower MSI-H frequency of 10%–20% [ 27 32 ].…”
Section: Discussionmentioning
confidence: 99%